Trauma exposure and factors associated with ICD-11 PTSD and complex PTSD in the Lithuanian general population. (December 2022) - Kvedaraite, Monika; Gelezelyte, Odeta; Kairyte, Agniete; Roberts, Neil P; Kazlauskas, Evaldas
Background: After the inclusion of a novel diagnosis of Complex Posttraumatic Stress Disorder (CPTSD) in the 11th edition of the International Classification of Diseases (ICD-11), there is a growing need for research focused on not only studying the underlying risk factors of this disorder but also differentiating the risk factors of Posttraumatic Stress Disorder (PTSD) and CPTSD to understand better the factors leading to CPTSD onset and symptom maintenance. Aims: This study aimed to explore the prevalence of traumatic experiences, trauma-related disorders and risk factors associated with ICD-11 PTSD and CPTSD in a population-based Lithuanian sample using the International Trauma Questionnaire (ITQ). Methods: The study sample included 885 participants (age M [ SD ] = 37.96 [14.67], 63.4% female). The Life Events Checklist was used to measure trauma exposure, PTSD and CPTSD symptoms were measured by the Lithuanian ITQ version. The Disclosure of Trauma Questionnaire (DTQ) was used to measure the urge or reluctance to talk about trauma. Results: The prevalence of at least one traumatic experience in the study sample was 81.4%. The prevalence of PTSD and CPTSD among the general population in Lithuania was 5.8% and 1.8%, respectively. Accumulative lifetime trauma exposure, sexual assault and assault with a weapon were significant predictors for both PTSD and CPTSD. Participants from the CPTSD group reported greater reluctance to disclose trauma and stronger emotional reactions than no diagnosis and PTSD groups. Results also indicate that the Lithuanian ITQ version is a valid measure for screening PTSD and CPTSD in the general population. Conclusion: Previous history of trauma and interpersonal trauma were associated with posttraumatic stress disorders but did not differentiate between PTSD and CPTSD in our study. However, social trauma-related factors, such as trauma disclosure, were associated with stronger CPTSD symptoms.